Thoughts about police tactics (Academic Journal of Internal Affairs, 2020)
Police tactics is a very important but neglected topic. There are just a few written documents about it, there is no schoolbook with comprehensive information about it, that’s why the education of police tactics is at low level. It’s probably related to the knowledge of the Hungarian police officers, which is not so perfect, I think. We need to collect all the knowledge we have about police tactics; we need to update it, we need to look for new information, and then we need to educate it at a higher level. My first step is determination of the concept police tactics.
Keywords: police tactics; neglected; determination; education